2021
DOI: 10.28991/esj-2021-sper-05
|View full text |Cite
|
Sign up to set email alerts
|

The Bayesian Confidence Interval for Coefficient of Variation of Zero-inflated Poisson Distribution with Application to Daily COVID-19 Deaths in Thailand

Abstract: Coronavirus disease 2019 (COVID-19) has spread rapidly throughout the world and has caused millions of deaths. However, the number of daily COVID-19 deaths in Thailand has been low with most daily records showing zero deaths, thereby making them fit a Zero-Inflated Poisson (ZIP) distribution. Herein, confidence intervals for the Coefficient Of Variation (CV) of a ZIP distribution are derived using four methods: the standard bootstrap (SB), percentile bootstrap (PB), Markov Chain Monte Carlo (MCMC), and the Bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, Srisuradetchai et al [18] proposed the profile-likelihood-based confidence interval for the geometric parameter of a ZIG distribution. Junnumtuam et al [19] constructed Wald confidence intervals for the parameters of a ZIP model; in an analysis of the number of daily COVID-19 deaths in Thailand using six models: Poisson, NB, geometric, Gaussian, ZIP, and ZINB, they found that the Wald confidence intervals for the ZIP model were the most suitable. Furthermore, Srisuradetchai et al [20] proposed three confidence intervals: a Wald confidence interval and score confidence intervals using the profile and the expected or observed Fisher information for the Poisson parameter in a ZIP distribution; the latter two outperformed the Wald confidence interval in terms of coverage probability, average length, and the coverage per unit length.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Srisuradetchai et al [18] proposed the profile-likelihood-based confidence interval for the geometric parameter of a ZIG distribution. Junnumtuam et al [19] constructed Wald confidence intervals for the parameters of a ZIP model; in an analysis of the number of daily COVID-19 deaths in Thailand using six models: Poisson, NB, geometric, Gaussian, ZIP, and ZINB, they found that the Wald confidence intervals for the ZIP model were the most suitable. Furthermore, Srisuradetchai et al [20] proposed three confidence intervals: a Wald confidence interval and score confidence intervals using the profile and the expected or observed Fisher information for the Poisson parameter in a ZIP distribution; the latter two outperformed the Wald confidence interval in terms of coverage probability, average length, and the coverage per unit length.…”
Section: Introductionmentioning
confidence: 99%